2015
DOI: 10.1186/s13054-015-1011-9
|View full text |Cite
|
Sign up to set email alerts
|

Early goal-directed resuscitation of patients with septic shock: current evidence and future directions

Abstract: Severe sepsis and septic shock are among the leading causes of mortality in the intensive care unit. Over a decade ago, early goal-directed therapy (EGDT) emerged as a novel approach for reducing sepsis mortality and was incorporated into guidelines published by the international Surviving Sepsis Campaign. In addition to requiring early detection of sepsis and prompt initiation of antibiotics, the EGDT protocol requires invasive patient monitoring to guide resuscitation with intravenous fluids, vasopressors, r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
37
0
4

Year Published

2016
2016
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 54 publications
(43 citation statements)
references
References 89 publications
2
37
0
4
Order By: Relevance
“…In contrast, the study by Ammerlaan et al, mainly conducted in European hospitals and using basically the same BSI definitions as in our study, showed that nosocomial BSIs due to antibiotic-resistant bacteria increased [21]. Similar findings have been reported from a large study in the US [5, 4]. Sweden has one of Europe’s lowest outpatient antibiotic consumption [43].…”
Section: Discussionsupporting
confidence: 84%
“…In contrast, the study by Ammerlaan et al, mainly conducted in European hospitals and using basically the same BSI definitions as in our study, showed that nosocomial BSIs due to antibiotic-resistant bacteria increased [21]. Similar findings have been reported from a large study in the US [5, 4]. Sweden has one of Europe’s lowest outpatient antibiotic consumption [43].…”
Section: Discussionsupporting
confidence: 84%
“…The Surviving Sepsis Campaign (SSC) guidelines proclaimed some components of EGDT as the standard treatment for patients with sepsis and septic shock (2,9). However, the beneficial effect of EGDT has been challenged by several large trials (10,11), which will be discussed in the following sections.…”
Section: Early Goal Directed Therapy (Egdt)mentioning
confidence: 99%
“…3134 SERRI’s second responders use standardized protocols, but, for most sites, the adequacy and timing of their implementation must be obtained by means of laborious chart review (time elapsed between a positive screen [T 0 ] and notification of a second responder; time elapsed between T 0 and the arrival of the second responder; time elapsed between T 0 and the orders for fluid resuscitation, cultures, lactic acid measurement, and antibiotics). The difficulty of getting these data means that it is possible to establish compliance with the sepsis care protocols (analogous to a “pill count” in a drug study) only for a sample of SERRI patients.…”
Section: Key Learningsmentioning
confidence: 99%